Integration of diesel plant into a hybrid power system using power pinch analysis - Mohammad Rozali, N.E. (Elsevier Ltd, 2016)
Diesel power systems are one of the schemes for energy supply generation. However, they are mostly associated with difficulties of emission control and cost of the maintenance on top of the diesel fuel cost. Some of these problems can be reduced by incorporating renewable energy such as wind turbines and solar PV along with the existing diesel station. Hybrid systems provide clean and reliable power supply, and can be more cost-effective than sole diesel systems. This paper assesses the feasibility of expanding an existing diesel power plant into a hybrid power system (HPS) using Power Pinch Analysis (PoPA). A HPS configuration developed using PoPA methodology can provide close-to-optimal solar and wind electricity supplies while minimising the diesel generation. Results show that a HPS that combines solar and wind system with diesel power generation can provide significant diesel fuel savings while satisfying the demands at a reasonable cost. Â© 2016 Elsevier Ltd